Dinossauros na literatura para crianças no Brasil - Sales, Lana Luiza Maia Feitosa (2019)
The present thesis aims to identify, primarily, the way how the paleontological knowledge related to dinosaurs is articulated into Children's Literature available in the Brazilian market, and how they oscillate between the scientific and the fictional character. This thesis also brings an interdisciplinary view – which yet was little explored – relating literature art to paleontological science. This investigative originality describes the importance of the research’s issue (and the reflections brought by it), that was made from the analysis of 76 verbal e visual texts and their authors For this work were selected children's books printed and available in the Brazilian market, with textual narratives where there are dinosaurs as protagonists, excluding manuals, atlases, encyclopedias, albums with popups, minibooks, comics, sound and others interactive books, and those based on movies or television series, as well as paid editions by their authors. It was verified that most of the texts (55) were from the 21st Century. A dominance of foreign texts (54) over the texts from Brazil (22) was as well observed. It was also found that, in general, while national editions were made in A5 brochure paper and written mostly by man, in translated books from other countries, there was a predomination of great format and hard cover books written mainly by reputed women. The theme ‘dinosaurs interactions with today’s animals’ was found only in national books. On the other hand, subjects like ‘magic’ and ‘museum’ were present only in foreign author’s histories. Among the translated texts, it was found a preference for themes such as ‘dinosaurs as toys’ or ‘dinosaurs as pets’. Narratives with dinosaurs brought to the urban modern world or even living in their own habitat were also common. Traditional themes, such as ‘living a dream’ or ‘entering a time machine’ are equally found inside Brazilian and foreign authors books. The ten most cited genera are †Tyrannosaurus (81,5%), †Triceratops (almost 58%), †Stegosaurus (50%), †Diplodocus (almost 37%), †Brontosaurus (31,5%), †Allosaurus and †Ankylosaurus (almost 29%), †Brachiosaurus (a little more than 26%), †Apatosaurus (a little more than 23%) and †Velociraptor (21%). The Brazilian dinosaur genera are mentioned only in three of all the books studied. This may be explained possibly because only about 28% of the books are Brazilian, of which 60% were written until 1997 (when only two species of Brazilian dinosaurs had been described), plus, dinosaurs were very few known by the Brazilian great public until the beginning of this Century. This reduced offer of information let a great number of children and young people without knowing about the Brazilian dinosaurs. The time does not seem to be important in the ficcional narrative with dinosaurs, as it is not mentioned in 63 of them. Just 23 (about 30%) of the books have clear educational intents, generally, speaking about the dinosaurs diversity and characteristics. However, seven books destined to children who are recent readers (almost 25%) seek to teach good habits like hygiene and living together rules. Some of the youth’s books with obvious didactical purposes, but with a creative and humorous narrative – and other tools like polysemy, multimodal texts, polyphonic and comic illustrations –, can be worked in the classroom with lightness and great advantage in the learning about dinosaurs. This kind of book may be an inspiration in interactive classes, making the teaching more creative and stimulating, so students can practice insights for the solution of scientific enigmas, as long they acquire the knowledge about geological and temporal dimension. Thus, it is concluded that dinosaurs can be perfectly adapted as characters for fantastic stories, they have been inspiring writers in the construction of original children and youth narratives, in which it is also possible to transmit scientific knowledge, and still arouse the taste for the study of these fossils, all of it without interfering in the literary quality of the work, as some of the books analyzed here can be a proof of.